Diseño de una guía metodológica para incrementar el coeficiente intelectual de los niños de nivel inicial y primer año de preparación de educación general básica en el centro educativo particular marqués de la fayette en la provincia de Pichincha cantón Quito periodo 2013-2014 - Recalde Morán, Kenia Jhosfaira (2015)
This research has been conducted in order to determine active methodological strategies for teaching and learning through the implementation of a methodological guide that allows through dynamic, innovative and educational activities, improve IQ in children and early Education First year of Basic General Education Preparation, Education Center Marquis de La Fayette in the canton of Quito, by applying principles and scientific, technical and linguistic level to improve children's learning standards in different subjects. This study makes it possible to overcome the problems of improving learning through creative activities and fun interest in learning new things, exercising your brain and increase your IQ, not only with theoretical and practical activities, but with sequences of physical exercises to keep them awake much and energy throughout the school day, allowing at the same time improve the academic performance of students, allowing them to be motivated and confident in the development of their educational process.